Protection of inactive intranasal ántrax vaccine to Bacillus anthracis infection - Adin Priadi; Lily Natalia; Rahmat S. Adji (Indonesian Center for Animal Research and Development (ICARD), 2010)
Ánthrax is an endemic zoonotic disease distributed in many parts of Indonesia. Although vaccination program has been implemented in many areas, cases are still frequently reported. Farmers are reluctant to vaccinate their livestock since spore vaccine used in the field often cause side effects and death of the animals. To overcome this problem, an inactive vaccine composes of Bacillus anthracis toxins, cell wall and capsule subunits was developed. B. anthracis Sterne strain (34F2) was selected to produce toxins and cell walls. Local Bacillus anthracis isolated from Citaringgul was used to produce capsule as the Polymerase Chain Reaction (PCR) revealed that this isolate poses cap gene encoding for capsule. Two vaccines compose of 15 μg toxoid, 30 μg of capsule, 15 μg of cell wall and 30 μg toxoid, 60 μg of capsule, 15 μg of cell walls were designated as vaccine I and vaccine II respectively. For each experiment, 10 mice were nasally immunized by placing 5 μl of vaccine into each nare 3 times at 2-week intervals. A group of 10 mice were unvaccinated and used as control. Blood was collected fortnightly to monitor antibody responses. All mice were challenged with 2 x 105 B. anthracis Sterne spores injected subcutaneously two weeks after the last vaccination. Two weeks after vaccination of antibodies to B. anthracis toxin, capsule and cell wall were detected in dot-blot assay. Mice that were immunised intranasally with chitosan adjuvanted vaccine developed high IgG responses in sera as detected by ELISA, and the response was dose dependent. Vaccine II gave better response than vaccine I. Vaccine I and II protected mice from challenge at a rate of 60 and 80% respectively. This results showed that intranasal B. anthracis vaccine composes of toxin, capsule and cell wall with chitosan as an adjuvant gave a good protection against B. anthracis Sterne spores challenge in mice. Key Words: Inactive Intranasal Ántrax Vaccine, Protection, Bacillus anthracis, Mice